The effect of phasic versus combined neuromuscular electrical stimulation using the StimaWELL 120MTRS system on multifidus muscle morphology and function in patients with chronic low back pain: a randomized controlled trial protocol - Maryse Fortin; Daniel Wolfe; Geoffrey Dover; Mathieu Boily (BMC Musculoskeletal Disorders, 2022)
Abstract Background Neuromuscular electrical stimulation (NMES) is used to improve muscle strength clinically when rehabilitating various musculoskeletal disorders. However, the effects of NMES on muscle morphology and function in individuals with non-specific chronic low back pain (CLBP) have scarcely been investigated. Although research links deficits in the paraspinal musculature with subjective reports of pain and disability, it is unknown if treatment with NMES can help reverse these deficits. Therefore, the primary aim of this study is to compare the effects of two muscle therapy protocols with a medium-frequency electrotherapy device (the StimaWELL 120MTRS system) on multifidus muscle morphology and function in CLBP patients. The secondary aims are to determine the effects of these protocols subjective reports of pain intensity, pain interference, disability, and catastrophizing. Methods A total of 30 participants with non-specific CLBP, aged 18–60, will be recruited from local orthopedic clinics and databases. Participants will be randomized (1:1) to either the phasic or combined (phasic + tonic) muscle therapy protocols on the StimaWELL 120MTRS system. Participants will undergo 20 supervised electrotherapy treatments over a 10-week period. The primary outcomes will be multifidus morphology (e.g. cross-sectional area (CSA), fat infiltration) and function (e.g., contraction measured via %thickness change from a rested to contracted state, and stiffness at rest and during contraction). Secondary outcomes will include pain intensity, interference, disability, and catastrophizing. Both primary and secondary outcomes will be obtained at baseline and at 11-weeks; secondary outcomes measured via questionnaires will also be obtained at 6-weeks, while LBP intensity will be measured before and after each treatment. Paired t-tests will be used to assess within-group changes for all primary outcome measures. A two-way repeated-measures analysis of variance will be used to assess changes in secondary outcomes over time. Discussion The results of this trial will help clarify the role of medium-frequency NMES on lumbar multifidus morphology and function. Trial Registration NCT04891692, registered retrospectively on May 18, 2021.